Transient Heat Transfer Characteristics of Round Jet Impacting on Inclined Concave Cylindrical Surface Based on Thermochromic Liquid Crystal - Ming-yang, Liu; Shi-nan, Chang (IET Conference Proceedings, 2018)
The transient heat transfer characteristics of a single circular hole jet impacting concave cylinder were obtained by thermochromic liquid crystal. In the study, the airflow Reynolds number Re, the impact distance to nozzle diameter ratio L/d and the jet impact angle α were changed. The color change process of the concave surface of the experimental part was photographed by the industrial camera. The local Nusselt number NuD distribution was calculated. The results show that the distribution of NuD for the initial phase of the jet impingement is bell type in a radial direction along the impact center. And with the impact process, the Nusselt number at the stagnation point Nus decreases gradually, where the maximum difference is 26.9%. When Re increases and L/d close to 4, the second peak is gradually obvious. As α increases, the second peak moves to the region of r / d ⩽ O gradually. In addition, the linear relationship between the Re, L/d, α and Nus is obtained by linear analysis.